Managing change at work : leading people through organizational transitions - Scott, Cynthia D (Crisp Pub. Menlo ParkUS, 1995)
Provides the skills which managers need for understanding the process of change in their organizations; and for supporting their teams through changes. Provides worksheets so that readers can be actively involved as they study.